Design of Three-Axis Orthogonal Magnetic Gradient Sensor based on Differential Structure - Wang, Qijun; Su, Can; Liu, Hang; Zhou, Rui (Scientific Journal of Technology, 2026)
To address the challenges faced by traditional fluxgate magnetic gradient meters in achieving multi-axis synchronous measurement, such as orthogonality among the three axes, channel consistency, and structural integration, a highly integrated magnetic gradient sensor design based on a center-symmetric orthogonal structure is proposed. The design integrates the three-axis differential sensing units into a compact whole through an integrated three-dimensional orthogonal coil frame, achieving a high degree of physical parameter matching among the channels. On this basis, combined with the reverse series differential detection mechanism and multi-channel synchronous processing circuit, the system’s ability to suppress common-mode interference and signal consistency is effectively enhanced. The paper elaborates in detail on the sensor’s structural design, working principle, parameter optimization, and signal processing flow. The effectiveness of the design in improving channel consistency and enhancing orthogonal measurement accuracy is verified through finite element simulation.